Protein synthesis : methods and protocols - Martin, Robin (Methods in molecular biology (Clifton, N.J.), 1998)
The synthesis of proteins from 20 or so constituent amino acids according to a strictly defined code with an accuracy of better than 1 in 10,000 at most loca tions is arguably the most complex task performed by cells. Protein Synthesis collects together methods and protocols covering a range of different approaches towards understanding how the cellular machinery accomplishes this task and how these ftinctions might be harnessed by the biotechnology industry to generate novel and useful proteins. The era in which the components of the translational machinery were being catalogued is over. This volume gathers together protocols that focus on preserving and describing the dynamic function as closely as possible. The need to understand exactly how ribosomes are positioned on messages or where tRNA molecules, translation factors, or control proteins are bound, has been appreciated by many of the authors. Several chapters that explore the fidelity and processivity of translation reflect this belief. Moreover, the fundamental importance of rRNA at the heart of the ribosome is a strong theme in a number of the protocols. These articles include in vitro and in vivo systems from bacterial, fungal, plant, and animal systems. Overall, Protein Synthesis might be characterized by the novelty of the approaches employed to illuminate the inner workings of the protein synthetic machinery as well as by the inventiveness of the attempts to harness these reactions for biotechnological applications.